ANALYSIS OF THE INFLUENCE OF CHARACTERISTICS, WORK MOTIVATION AND TRAINING ON THE PERFORMANCE OF DRUG AND MEDICAL DEVICE MANAGEMENT OFFICERS IN COMMUNITY HEALTH CENTER IN HULUL SUNGAI UTARA DISTRICT - Noorfitriya Hayani; Hary Soegiri (Jurnal Ekonomi, 2023)
This study aims to determine the effect of Characteristics, Work Motivation and Training on the Performance of Drug and Medical Device Management Officers at Health Centers in Hulu Sungai Utara Regency. Respondents in this study were Drug and Medical Device Managers at Health Centers in Hulu Sungai Utara Regency with a sample of 52 respondents. Data collection techniques were through interviews, questionnaires and documentation. Data analysis techniques used in this study were validity test analysis, reliability test, classical assumption test, multiple regression analysis and hypothesis test analysis. The results of the study showed that characteristics, work motivation and training influenced the performance of drug and medical device management officers at health centers in Hulu Sungai Utara district by 72.5%.